Geopolymer Composite Coatings Based on Moroccan Clay and Sands for Restoration Application - El Khomsi, Anass; Gharzouni, Ameni; Farges, Remi; Duport, Patrice; Idrissi Kandri, Nourredine; Zerouale, A.; Rossignol, Sylvie (Frontiers in Chemical Engineering, 2021)
This study aims to explore geopolymer binders and mortars based on local Moroccan clays and sands as coatings for the restoration of historical monuments in Morocco. For this, five substrates, one geopolymer binder, and two geopolymer mortars were investigated. The characterization of substrates reveals differences in terms of pH value, capillarity, contact angle, and surface roughness. These differences affect the coating thickness, which also depends on the viscosity, liquid to solid ratio, and granular skeleton of the geopolymer coating. High adhesive strength values (up to 9 MPa) were obtained on limestones. However, these values decreased with the increase of relative humidity. In the case of Fez stone, a stable adhesive strength value (3 MPa) was evidenced for all the coating formulations and at different storage conditions confirming the suitability of coating based on metakaolin, Moroccan clays, and sands for restoration applications.